PENINGKATAN MOTIVASI BELAJAR MAHASISWA PADA MATA KULIAH KONSEP DASAR MATEMATIKA MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING - Yudha, Chrisnaji Banindra (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
Abstract : This study aims to increase motivation on the subject of basic mathematical concepts using Contextual Teaching And Learning (CTL) in Odd Semester Academic Year 2016/2017 Primary School Teacher Education Study Program STKIP Kusuma Negara Jakarta .This research is a classroom action research in a collaborative manner. Classroom Action Research (PTK) is done in 2 cycles, where each cycle there are 4 stages include; a). Planning), b). Acting, c).Observing,d).Reflecting. Increased student's motivation to learn can be seen from before action, that the average motivation of students at 54% with low category, in the first cycle increased to 69% with the category of being,and in cycle II increased again to 84% with high category. So in the second cycle more than 80% of students have high motivation. Students have a need in following learning basic concepts of mathematics, interest, curiosity and joyful to follow lectures basic concepts of mathematics. Keywords: Motivation And Contextual Teaching And Learning (CTL)